114 THE EFFECTIVENESS OF A 26-WEEK CLASS AND HOME-BASED OTAGO EXERCISE PROGRAMME ON BALANCE CONFIDENCE AND PHYSICAL PERFORMANCE IN OLDER ADULTS. (25th October 2022) - Curley, M; Brady, S; Tyndall, F; McVeigh, J; McCullagh, R
Abstract: Background: Falls have a substantial burden on the Irish economy and on the individual. The Otago Exercise Programme (OEP) is a cost-effective falls prevention programme that can prevent 35% of falls. This study aims to evaluate the effectiveness of a 26-week modified OEP using a combined delivery approach of physiotherapists and Exercise Therapists (ET) on balance confidence and physical performance in older adults in rural Ireland. Methods: Study-design: A prospective pre-post single arm intervention study. Older adults (≥60 years) were recruited from HSE waiting lists for the OEP which consisted of a group-class (1x/week) and a home OEP (3x/week). Participants were assessed at baseline, 6, 16 and 26 weeks. Outcome measures (OMs) were compared pre and post intervention using Paired T-Tests and Wilcoxon Signed Ranks tests. A repeated-measures ANOVA compared OMs across the time points. Results: Improvements were detected in the CONFbal scale (diff = 2.12, 95% CI=1.353-2.803, p<0.01), 30-second sit-to-stand (diff = 3.49, CI= 2.361-4.201, p<0.01), timed-up and go (diff = 2.38, CI=8.08-12.0, p<0.01), functional reach (diff = 9.158, CI=6.758-11.294, p<0.01), 180° turn (diff = 1.04, CI=3-5, p<0.01), and the four-test balance scale (diff = 0.61, CI=1.0-3.0, p<0.01). Significant changes are noted for each measure (p<0.05) with small-moderate positive effects (ηp2=0.32-0.512). The most significant changes in the 180° turn are seen between week-0 (4.92 ±1.784) and week-6 (4.44 ±1.258) followed by a plateau in results. Conclusion: Confidence and physical performance improved significantly pre and post intervention, suggesting the physiotherapist and ET combined delivery of the programme is effective. Static and dynamic balance improvements may plateau after 6-weeks of the OEP suggesting the participants may not have been adequately challenged. Lower limb strength and mobility continued to improve throughout suggesting the modified OEP is an effective intervention for older adults in Ireland.